Desigualdades socioespaciais e sua relação com os estudantes da classe trabalhadora: beneficiários do auxílio moradia e seu uso do espaço em Campo Grande/MS - Rodrigo Domingues da Costa (2023)
The present work aims to demonstrate how students who use housing assistance, a type of student assistance, perceive socio-spatial inequalities through their relationship with the use of urban space. This work aims to demonstrate how the process of reproduction of urban space occurs, provided to students included in the group of beneficiaries. For a better outline of this research, the object of analysis will be a total of 239 students, who receive housing assistance, enrolled at Cidade Universitária, in Campo Grande, in the year 2021. The type of research developed in this work is xploratory, despite Having the use of bibliographical research as a strategy, there is a need to study different axes and bring them together in order to give meaning to the text developed. Terms and concepts such as student assistance, work, assistance policies and socio-spatial inequality will be addressed with a theoretical basis through the use of primary and secondary sources, such as: scientific articles; dissertations and theses in Postgraduate Programs in Education, Social Work and Geography; in the same way as books; periodicals; articles in magazines; forms from the institution under analysis, and questionnaire and interviews developed to complement information from UFMS, however, the connection between student assistance policies and reproduction of urban space by beneficiaries, intensifying processes of socio-spatial inequality had not yet been directly addressed . The objective of this research is to analyze which portions of the city are occupied by these students, and how these individuals reproduce and consume space. Taking into account the dialectical process of reproduction of urban space, relating not only to the material sense, but to the territorially projected power relations and socio-spatial practices inscribed in the space. Thus, the form of unequal use by students assisted by student assistance is a reflection of an also unequal system that affects, more abruptly, the working class in our country, the result of contradictory relations of capital reproduction. Keywords: working class students; housing assistance; socio-spatial inequality.